Enhanced Activity of Hydrochlorination of Acetylene Using Melamine-Modified Activated Carbon Supported Gold Catalyst - Dai, Bin; Ma, Ning; Zhang, Haiyang; Wang, Xugen (Asian Journal of Chemistry, 2013)
A series of modified activated carbon (MAC) was prepared by impregnating with a aqueous solution of melamine and heating under N2 flow at diffferent temperatures. The surface structure of the prepared MAC was characterized by BET, elemental analysis, SEM, FT-IR and XPS. The results of the single carrier activity test showed that MAC exhibited higher activity than activated carbon. Characterization results indicated that the enhanced carrier performance of MAC could be attributed to the presence of nitrogen-containing groups. Subsequently, the supported gold catalysts Au/activated carbon and Au/MAC-0.8-650 were prepared by impregnating with a H[AuCl4]·4H2O solution which was dissolved in aqua regia. Under the reaction conditions of feed volume ratio V (HCl)/V (C2H2) = 1.15, temperature 180 ºC, C2H2 hourly space velocity (GHSV) 360 h-1 and gold loading of 0.2 wt %, the acetylene conversion and vinyl chloride monomer selectivity of Au/MAC-0.8-650 were 95 and > 99.91 %.